2017
DOI: 10.1186/s12864-017-3592-y
|View full text |Cite
|
Sign up to set email alerts
|

A reference gene set for sex pheromone biosynthesis and degradation genes from the diamondback moth, Plutella xylostella, based on genome and transcriptome digital gene expression analyses

Abstract: BackgroundFemale moths synthesize species-specific sex pheromone components and release them to attract male moths, which depend on precise sex pheromone chemosensory system to locate females. Two types of genes involved in the sex pheromone biosynthesis and degradation pathways play essential roles in this important moth behavior. To understand the function of genes in the sex pheromone pathway, this study investigated the genome-wide and digital gene expression of sex pheromone biosynthesis and degradation g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 110 publications
3
47
0
Order By: Relevance
“…SlitGSTe clustered with lepidopteran GSTe functionally involved in insecticide conjugation and protection against oxidative stress in B. mori, H. armigera, S. litura , and S. exigua (Huang et al, 2011; Yamamoto et al, 2013; Liu et al, 2015b; Xu et al, 2015; You et al, 2015; Zhou et al, 2015; Wan et al, 2016; Zhang et al, 2016; Hirowatari et al, 2017; Labade et al, 2018). Moreover, three P. xylostella GSTe are also preferentially expressed in the antennae (He et al, 2017), suggesting a potential role in olfaction. SlitGSTe9 and SlitGSTe6 were predominantly expressed in the adult antenna, legs and larval midgut; in addition, SlitGSTe15 was restricted to adult life stages and restricted to chemosensory tissues.…”
Section: Discussionmentioning
confidence: 99%
“…SlitGSTe clustered with lepidopteran GSTe functionally involved in insecticide conjugation and protection against oxidative stress in B. mori, H. armigera, S. litura , and S. exigua (Huang et al, 2011; Yamamoto et al, 2013; Liu et al, 2015b; Xu et al, 2015; You et al, 2015; Zhou et al, 2015; Wan et al, 2016; Zhang et al, 2016; Hirowatari et al, 2017; Labade et al, 2018). Moreover, three P. xylostella GSTe are also preferentially expressed in the antennae (He et al, 2017), suggesting a potential role in olfaction. SlitGSTe9 and SlitGSTe6 were predominantly expressed in the adult antenna, legs and larval midgut; in addition, SlitGSTe15 was restricted to adult life stages and restricted to chemosensory tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies revealed insect UGT activity in different tissues and indicated that UGTs play diverse roles in olfaction, detoxification, pigmentation, digestion, and sequestration. [28][29][30][31][32][33] The detoxification of xenobiotics by UGTs has been further described in Helicoverpa armigera (Hübner) and Heliothis virescens (Fabricius), and Zygaena filipendulae (L.) using the heterologous expression systems. 34,35 In A. gossypii, the overexpression of UGTs was observed in thiamethoxam-and imidacloprid-resistant populations.…”
Section: Discussionmentioning
confidence: 99%
“…The target compound was obtained using column chromatography. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). These analogs were obtained from (11Z)-hexadecen-1-ol (0.51 g, 2.1 mmol), 4-dimethylaminopyridine (0.01 g, 81.8 μmol), triethylamine (0.32 g, 3.2 mmol) and the corresponding anhydride using the synthetic method of 2.…”
Section: (11z)-11-hexadecenal (3)mentioning
confidence: 99%
“…Currently, most studies on sex pheromone analogs focus on their mechanism of action . As for P. xylostella , research mainly focuses on receptor protein and gene expression analysis for the synthesis and decomposition of sex pheromones . In this study, Z 11‐16: Ac and Hexadecyl acetate (16: Ac) were used as the parent structures and 23 sex pheromone analogs were designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation